Dores e cores nas mal traçadas linhas dos devotos do Padre Cícero: as trocas linguísticas instauradas entre o discurso eclesial e o discurso epistolar dos romeiros - Ribeiro, Maria das Graças de Oliveira Costa (2014)
This study is concerned with analyzing the letters sent by the devotees tothe religious patriarch, Father Cicero, checking as is the relationship of linguistic exchanges between the pilgrims and the Father Cicero through the issuance of letters; and, between the Church and the pilgrims, through homilies uttered these devotees, focusing on the appeals contained therein, for, then, to define a parameter between the requirements contained in the letters and the religious discourse of the Church workers in the liturgical celebrations in view of social and religious demands of the market in question. Our purposes resided in understanding the causes that lead to the production of the letters by devotees, holding us in prayers of intercession to the Father Cicero. Finally, check and understand how is the process of inter - relationship between the writing of devotee and the clerical discourse, with regard to meeting this demand, noting especially the game force a religious field, based on postulates of Pierre Bourdieu (2008), to conceive the communicative act as linguistic exchanges, surpassing the sign and therefore decipherable speech character as well as the interactive strength of the wording and voice advocated by Paul Zumthor (2010) e Bakhtin (2006). Regarding the composition of the corpus, were determined, as the universe of research, letters of pilgrims, sent to Father Cicero, deposited in his own tomb, as well as in the Church of the Horto (Gethsemane) in Juazeiro do Norte-CE (Brazil); beyond religious sermons intended for pilgrims during the massin pilgrimage time